Tindak Pidana Penganiayaan dalam Fiqh Jinayah dan Hukum Pidana Indonesia - Eko Wahyudi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
Often the violence perpetrated by a group of people against suspected perpetrators of certain acts of crime, sometimes even people doing things that are beyond the boundaries of humanity, called "citizen vigilantism". This paper is a description of the persecution in fiqh jinayah and positive criminal law. The conclusion of this paper is that in fiqh jinayah persecution consists of (1) due to deliberate and (2) due to negligence, whose object consists of: (1) regarding parts of the human body, (2) removes the meaning of limbs, wounds on the head, (4) injuries to other limbs, and (5) other injuries, while the punishment is qisas, if forgiven then replaced diyah, and if forgiven then replaced ta'zir. Whereas in the Indonesian Penal Code, persecution consists of due to "deliberate" or "negligence", which is divided into (1) ordinary abuse, (2) minor persecution, (3) plain old-planned persecution, (4) severe persecution and (5) persecution weight with a planned first.